A review of adolescent nutrition in South Africa: transforming adolescent lives through nutrition initiative. Issue 4 (1st October 2020) - Wrottesley, Stephanie V; Pedro, Titilola M; Fall, Caroline H; Norris, Shane A
Abstract : Objective: In South Africa, urbanisation is associated with substantial burdens of adolescent overweight and obesity, making teenagers vulnerable to longer-term non-communicable diseases. In addition, as potential future parents, the nutritional status of adolescents is increasingly recognised as a key driver of health and well-being in the next generation. This review reported on the available literature examining nutritional status and dietary intakes and practices, as well as their determinants, in South African adolescents. Study design and methods: Medline (Pubmed), Web of Science and EMBASE were searched for relevant articles published between 1994 and May 2018. Applicable search terms and phrases were identified in study titles and/or abstracts and full-text articles were reviewed according to inclusion/exclusion criteria. Data were extracted according to specific review objectives. Results: A total of 67 relevant studies were identified. Only one study used a biochemical marker to describe adolescent nutritional status (vitamin D status; 25(OH)D). Overweight and obesity prevalence increased in South African adolescents over the reference period, with national increases of 6% in boys and 7% in girls between 2002 and 2008. Girls and urban-dwellers were particularly vulnerable to excess adiposity. Dietary intakes demonstrated a transition towards energy-dense, processed foods high in sugar and fat, but low in essential micronutrients. Food choices were driven by the adoption of obesogenic behaviours in the teenage years, including irregular breakfast consumption and fewer family meals, increased snacking and low levels of physical activity. Conclusion: South African adolescents—particularly girls—are increasingly burdened by obesity as a result of urbanisation-associated shifts in dietary intake and eating behaviours. However, the implications for micronutrient status and long-term nutritional health are not known. Additionally, more data on the clustering of diet, activity and sedentary behaviours in adolescent boys and girls is needed, as well as on behaviour patterns to facilitate healthy growth and reduced adiposity.